(untitled) (American Journal of Islam and Society, 2009)
An encyclopedia is popularly thought of as presenting the sum of all knowledge, whether it be universal or on a specific topic. A moment’s reflection reveals, of course, that such an understanding does not quite get at the real concept, for there is no such thing as “all knowledge.” The historicalmoment will always define the extent of the knowledge that is available. The structural terms within which that knowledge is constructed – its headings and subheadings – are historically bound as well. One of the features – both admirable and disconcerting – of the Encyclopedia of Women & Islamic Cultures is how the work makes the reader aware of these factors: that this encyclopedia is, in fact, by its very act of being produced, defining a previously non-existent area of encyclopaedic knowledge and that the gaps in knowledge of the subject area, even after the production of the work, are substantial. Volume 4, “Economics, Education, Mobility and Space,” illustrates this point vividly. As can be seen by the volume’s heading, the overall encyclopedia is organized at the top level in themes. Within each volume, though, entries are organized alphabetically. The main topics covered are “Cities,” “Development,” “Economics,” “Education,” “Environment,” “Information Technologies,” “Migration,” “Poverty,” “Slavery,” “Space,” and “Tourism.” Since the ordering of the next level of headings is alphabetical as well, there is no particular organizational logic to the sequence of presentation. Under “Cities,” for example, the subheadings are, in order: “Colonial Cities,” “Homelessness,” “Informal Settlement,” “Islamic Cities,” “Urban Built Environments,” “Urban Identities,” and “Urban Movements.” It is difficult to ascertain whether any theoretical structure has dictated these subheadings ...